1991
DOI: 10.2307/1131174
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Functioning in Very Young Children: Understanding of Pictures and Models

Abstract: Before one can understand or use any symbol, one must first realize that it is a symbol, that is, that it stands for or represents something other than itself. This article reports 4 studies investigating very young children's understanding of 2 different kinds of symbolic stimuli--scale models and pictures. The data replicate previous findings that 2.5-year-old children have great difficulty appreciating the relation between a scale model and the larger space it represents, but that they very readily apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
206
5
19

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(249 citation statements)
references
References 16 publications
19
206
5
19
Order By: Relevance
“…In the only study we know of examining infants' learning from picture books, Ganea and DeLoache (2005) found that 18-month-olds, and some 15-montholds, extended a novel label learned for a novel depicted object to the real object. Moreover, from around 24 to 30 months of age, young children can use a photograph to locate a toy hidden in a room (DeLoache, 1991;DeLoache & Burns, 1994;Suddendorf, 2003).Early on, infants' and toddlers' ability to relate pictures to their referents is relatively tenuous and affected by iconicity, that is, by the degree of similarity between depiction and real object. For example, 9-month-olds engage in more manual exploration of highly iconic pictures (photographs) than less iconic pictures (drawings) (Pierroutsakos & DeLoache, 2003).…”
mentioning
confidence: 99%
“…In the only study we know of examining infants' learning from picture books, Ganea and DeLoache (2005) found that 18-month-olds, and some 15-montholds, extended a novel label learned for a novel depicted object to the real object. Moreover, from around 24 to 30 months of age, young children can use a photograph to locate a toy hidden in a room (DeLoache, 1991;DeLoache & Burns, 1994;Suddendorf, 2003).Early on, infants' and toddlers' ability to relate pictures to their referents is relatively tenuous and affected by iconicity, that is, by the degree of similarity between depiction and real object. For example, 9-month-olds engage in more manual exploration of highly iconic pictures (photographs) than less iconic pictures (drawings) (Pierroutsakos & DeLoache, 2003).…”
mentioning
confidence: 99%
“…Later, at around three years of age, children become able to use scale models and simple maps in the same manner (DeLoache, 1991;Liben, 1999;Marzolf & DeLoache, 1994; see also MacConnell & Daehler, 2004). Subsequently, children reveal understanding that photographs or drawings can represent their referents as they looked in the past rather than as they are currently (Robinson, Nye & Thomas, 1994;Thomas, Jolley, Robinson & Champion, 1999;Zaitchik, 1990).…”
mentioning
confidence: 99%
“…According to De Loache (1991), when someone looks at a picture, he will focus on the representation not the picture as an object. Therefore, although very young children might not appreciate photographs as much as adults, photographs and pictures are found to be much easier for young children to understand and to relate with the real object (see DeLoache, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%